2013
DOI: 10.1021/am401402x
|View full text |Cite
|
Sign up to set email alerts
|

Towards Tunable Sensitivity of Electrical Property to Strain for Conductive Polymer Composites Based on Thermoplastic Elastomer

Abstract: The use of conductive polymer composites (CPCs) as strain sensors has been widely investigated and various resistivity-strain sensitivities are desirable for different applications. In this study, the use of mixed carbon fillers and functionalized carbon nanotubes was demonstrated to be vital for preparing thermoplastic polyurethane (TPU)-based strain sensors with tunable sensitivity. To understand the strain sensing behavior, we carried out scanning electron microscopy (SEM), Raman spectroscopy, wide-angle X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
174
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(179 citation statements)
references
References 74 publications
(139 reference statements)
3
174
0
Order By: Relevance
“…[ 110 ] The dominant strain-responsive mechanism of the (CNTs or graphene)-polymer nanocomposites based strain sensors was discovered to be the tunneling effect. [ 34,35,62,71,82,90,107,108,110 ] Moreover, single CNT and monolayer graphene possess high tensile strength up to 40% and 30% with fully reversible structural geometry due to the energy absorption of the carbonic hexagonal honeycomb structure. [ 34,55,90 ] Therefore, CNTs and graphene could be regarded as elastic nanomaterials.…”
Section: Tunneling Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 110 ] The dominant strain-responsive mechanism of the (CNTs or graphene)-polymer nanocomposites based strain sensors was discovered to be the tunneling effect. [ 34,35,62,71,82,90,107,108,110 ] Moreover, single CNT and monolayer graphene possess high tensile strength up to 40% and 30% with fully reversible structural geometry due to the energy absorption of the carbonic hexagonal honeycomb structure. [ 34,55,90 ] Therefore, CNTs and graphene could be regarded as elastic nanomaterials.…”
Section: Tunneling Effectmentioning
confidence: 99%
“…Physical, chemical, biological, and environmental status of the human body could be monitored by various fl exible sensors with high effi ciency and minimum discomfort. [1][2][3][4][5][6][7][8][9] Stretchable strain sensors were fabricated through different processes including fi ltration method, [ 10,47,58,71,73,79,80 ] printing technology, [ 57,65,66,71 ] transferring and micromolding methods, [ 14,50,52,55,56,58,60 ] coating techniques, [ 49,54,61,63,72,78,79 ] liquid phase mixing, [ 12,51,52,60,62,71,77,81 ] and chemical synthesis methods. [ 14,55,56,76,82 ] We have recently reported highly stretchable and sensitive strain sensors based on the silver nanowires (AgNWs)-elastomer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…[108][109][110] Numerical simulations [111][112][113][114] were conducted to study the behavior of resistive strain sensors. For example, the resistive response for AgNW-PDMS sensor was highly correlated to the aspect ratio and density of AgNWs.…”
Section: Resistive Strain Sensorsmentioning
confidence: 99%
“…Sensitivity degradation has been reported in multiple studies related to polymer nanocomposites. Some authors have reported it for custom-made stress [32,33] and strain sensors [34], thus indicating that sensitivity degradation is not exclusive of FlexiForce sensors [35,36], but rather, a phenomenon related with the polymer composite itself. The authors have experimentally demonstrated that sensitivity degradation is a voltage-related phenomenon that only occurs when the contact resistance is the main sensing mechanism of the FSR, i.e., when V FSR is large enough [20].…”
Section: Error Sources and Types Of Error In Fsrsmentioning
confidence: 99%